Pengaruh Career Aspiration Terhadap Perceived Future Employability pada Mahasiswa (Sarjana dan Diploma) - Ikhsan Abdillah Prasetyo; Pratista Arya Satwika (Jurnal Ilmiah Psikologi Candrajiwa, 2025)
The high unemployment rate among university graduates highlights the importance of understanding psychological factors that enhance future employability. This study aims to investigate the effect of career aspiration on perceived future employability (PFE) among undergraduate and diploma students at Universitas Sebelas Maret. Using a quantitative survey approach, data were collected from 378 active students in the even semester of 2024/2025 (cohorts 2020–2024) selected through purposive sampling. The instruments used were the Indonesian version of the Perceived Future Employability Scale (24 items; α = 0.914) and the Korean Career Aspiration Scale-Revised (21 items; α = 0.870). Simple linear regression analysis revealed that career aspiration had a significant positive effect on PFE (β = 0.732; F = 188.144; p < 0.001). These results indicate that students with higher career aspirations are more confident about their future employment opportunities. The findings suggest the need for career guidance programs that strengthen career goal clarity and opportunity awareness to better prepare graduates for entering the workforce.